Catatonia Secondary to Sudden Clozapine Withdrawal: A Case with Three Repeated Episodes and a Literature Review - Bilbily, John (Case Rep Psychiatry, 2017)
A literature search identified 9 previously published cases that were considered as possible cases of catatonia secondary to sudden clozapine withdrawal. Two of these 9 cases did not provide enough information to make a diagnosis of catatonia according to the Diagnostic and Statistical Manual, 5th Edition (DSM-5). The Liverpool Adverse Drug Reaction (ADR) Causality Scale was modified to assess ADRs secondary to drug withdrawal. From the 7 published cases which met DSM-5 catatonia criteria, using the modified scale, we established that 3 were definitive and 4 were probable cases of catatonia secondary to clozapine withdrawal. A new definitive case is described with three catatonic episodes which (1) occurred after sudden discontinuation of clozapine in the context of decades of follow-up, (2) had ≥3 of 12 DSM-5 catatonic symptoms and serum creatinine kinase elevation, and (3) required medical hospitalization and intravenous fluids. Clozapine may be a gamma-aminobutyric acid (GABA) receptor agonist; sudden clozapine withdrawal may explain a sudden decrease in GABA activity that may contribute to the development of catatonic symptoms in vulnerable patients. Based on the limited information from these cases, the pharmacological treatment for catatonia secondary to sudden clozapine withdrawal can include benzodiazepines and/or restarting clozapine.